Innate immune tissue injury and murine HGA: tissue injury in the murine model of granulocytic anaplasmosis relates to host innate immune response and not pathogen load. - Scorpio, Diana G.; Von Loewenich, Friederike D.; Bogdan, Christian; Dumler, J. Stephen (Annals of the New York Academy of Sciences, 2005)
Anaplasma phagocytophilum is an obligate intracellular tick-borne bacterium that propagates within neutrophils and causes human and animal granulocytic anaplasmosis (HGA). In the murine model of HGA, host immune response plays a more important role in histopathologic lesions than does pathogen load. We examined the role of CYBB, NOS2, and TNFalpha as effectors of innate immune-related injury. Our hypothesis is that the innate immune response to A. phagocytophilum results in inflammatory histopathology, but does not control the pathogen.
CRIS-Team Scopus Importer:2024-02-26